2009
DOI: 10.1007/s10452-009-9256-5
|View full text |Cite
|
Sign up to set email alerts
|

Linking fish colonization rates and water level change in littoral habitats of a Venezuelan floodplain river

Abstract: Change in water level during the annual hydrologic cycle of tropical floodplain rivers results in continuous disassembly and reassembly of faunal communities in littoral habitat patches. As such, the rate of water level change should influence colonization rates of vagile organisms among habitat patches. We experimentally tested this hypothesis in a Venezuela floodplain river using artificial rocky patches as sampling units, water level change as the independent variable, and total number of individual fish th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
(31 reference statements)
1
13
0
Order By: Relevance
“…At both extreme of the gradient, communities are therefore more homogeneous which can be explained by the dominance of large scale processes [28]. For instance, water level reduction has been shown to influence community assemblage by influencing local individual abundances and by making it possible for species to colonize new local habitat patches [33], a process that can lead to community homogenization. Likewise, when the water level is very high, the presence of migratory species, dispersing over large distances, may homogenize fish communities.…”
Section: Discussionmentioning
confidence: 99%
“…At both extreme of the gradient, communities are therefore more homogeneous which can be explained by the dominance of large scale processes [28]. For instance, water level reduction has been shown to influence community assemblage by influencing local individual abundances and by making it possible for species to colonize new local habitat patches [33], a process that can lead to community homogenization. Likewise, when the water level is very high, the presence of migratory species, dispersing over large distances, may homogenize fish communities.…”
Section: Discussionmentioning
confidence: 99%
“…Different metacommunity structures can emerge from the relationship between species distributions and environmental gradients (Presley et al 2010) and in this study we showed that metacommunity structure may also change over time due to structural changes in their landscapes. Moreover, these structural changes can be related to predictable ecological processes related to the flood regime in this system, which directly affects the degree of environmental heterogeneity and landscape connectivity (Layman et al 2010). The floodplain fish metacommunity went from nested to quasi‐nested in the beginning of the wet season up to quasi‐Clementsian during the peak of the flood.…”
Section: Discussionmentioning
confidence: 99%
“…During the beginning of the season, the landscape has a considerable degree of heterogeneity because each temporary habitat patch presents particular physicochemical characteristics, low connectivity and distinct biota that are recruited from nearby permanent ponds (Layman et al 2010). Later in the flooding period, the ephemeral habitats become much more connected between them and with permanent waterbodies as well.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fish diversity (>300 species) is high, and fishes display a wide range of ecological attributes and life history strategies . These two rivers are characterized by a strongly seasonal hydrology with water levels typically fluctuating >5 m during an annual hydrological cycle (Arrington & Winemiller,2006;Layman et al, 2010). The Ventuari River is a tributary of the Orinoco River in Venezuela's Amazonas State characterized by clear water, low pH, and high fish diversity (> 400 fish species, Montaña et al, 2005).…”
Section: Study Sitementioning
confidence: 99%